교통사고후 절단된 시신경과 전자현미경소견 - 김인택; In Taek Kim; 송효철; Hyo Churl Soong; 최희규; Hee Kyu Choi (Daihan angwa haghoi jabji, 1998)
시신경은 해부학적 특징으로 쉽게 절단되지 아니한다. 시신경이 절단된 후 생체내에서 약 4.5개월동안 남겨진 시신경의 형태학적 소견을 전자현미경으로 관찰하고 하였다. 37세, 여자 가 교통사고로 좌측에 안면열상과 함께 안구돌출이 있었다. 전산화단층촬영상과 자기공명영상 에서 시신경이 절단되었음이 관찰되었다. 사고 당일 내원시 안저는 망막중심동맥폐쇄의 소견을보였다. 일차적으로 눈꺼풀봉합술을 실시하였다. 수술후 다음날 심한 전방출혈과 유리체출혈이 관찰되었다. 사고후 약 4.5개월 지난 뒤 안구적출술을 실시하고 전자현미경적 소견을 관찰하기 위하여 시신경을 채취하였다. 전자현미경적 소견에서 시신경섬유를 포함하는 축사과 수초의 층 상구조가 파괴되어 전혀 관찰되지 아니하였다. 신경교세포들도 발견되지 아니하였다. 신경교증 의 소견없이 결합조직형성세포와 탐식세포, 그리고 교원섬유로 구성된 섬유증이 주된 소견이었다. 즉, 절단된 시신경의 근위부는 신경교증으로 진행하는 것이 아니라 섬유증으로 진행됨을 알수 있었다. 이는 절단된 시신경을 둘러싸는 수막내 결합조직형성세포의 유입과 연막에서 시신경내로 뻗치는 섬유혈관성 격막에 존재하는 결합조직형성세포의 증식에 의한 것으로 추정된다(한안지 39:746~751, 1998). The optic nerve do not easily sever because of its anatomic status in the orbit. The purpose of this study is to investigate electron microscopic findings in the proximal portion of the severed optic nerve which remained in the orbit for about 4.5 months. Thirty seven-year-old woman showed the protruded eyeball and deep skin laceration following traffic accident. Computerized tomography and MRI demonstrated the complete severance in her left optic nerve. Her eyeball containing the proximal portion of the severed optic nerve was enucleated at about 4.5 months after traffic accident. Eletron microscopic findings showed several macrophages, fibroblast, and dense collagen fibers, which mean the fibrosis histopathologically. The fibrosis was the main pathologic outcome in the proximal portion of the severed optic nerve. We suggest that the process of the fibrosis could result from the incorporation of the fibroblast within the meninges around the optic nerve and the proliferation of the fibroblast within fibrovascular septa of the pia mater which extend into the optic nerve(J Koran Ophthalmol Soc 39:746~751, 1998).